PERSEPSI GURU TENTANG PELAKASAAN FUNGSI KEPEMIMPINAN KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA NEGERI KECAMATAN NANGGALO KOTA PADANG - Nilam Zahara, Puti Reno; Kadri, Hanif Al; Sabandi, Ahmad; Achyar, Novriyanti (Journal of Practice Learning and Educational Development, 2023)
This study aims to find out (1) describe the teacher's perception of the implementation of the principal's leadership function in Public Middle School, Nanggalo District, Padang City, (2) describe the implementation of the principal's leadership seen from the implementation of the instruction function from teacher perceptions in Nanggalo District Public Middle School, Padang City , (3) describes the implementation of the principal's leadership seen from the implementation of the consulting function from teacher perceptions in the Nanggalo District Public Middle School, Padang City, (4) describes the implementation of the principal's leadership seen from the implementation of the participation function from teacher perceptions in the Nanggalo District Public Middle School, Padang City, ( 5) describe the implementation of the principal's leadership seen from the implementation of the delegation function from the perceptions of teachers at SMP Negeri Nanggalo District, Padang City, and (6) describe the implementation of the leadership of the school principal from the implementation of the control function from teacher perceptions at SMP Negeri Nanggalo District, Padang City. This type of research is descriptive research. The population in the study were teachers at Nanggalo District Public Middle School, Padang City, totaling 57 samples. Sampling using simple proportional random sampling technique. The instrument used for research is a closed questionnaire using descriptive analysis. The results showed that: (1) the teacher's perception of the implementation of the leadership function based on instruction was very good with the highest average of 4.7, (2) the teacher's perception of the implementation of the leadership function based on consultative was very good with the highest average of 4.74, ( 3) the teacher's perception of the implementation of the leadership function based on participation is good with the highest average of 4.58, (4) the teacher's perception of the implementation of the leadership function based on delegation is very good with the highest average of 4.67, and (5) the teacher's perception of the implementation leadership function based on good control with the highest average of 4.58.